Organized Dissonance and Emotionality: A Case-Study of One Public Kindergarten in Moscow - Елена Алексеевна Конобеева (Journal of Economic Sociology, 2013)
The paper proposes a specific case-study of organizational form of public kindergarten. It is aimed at finding out in which way emotionality and formal rules match and how they influence the structure of kindergarten as an organization. Characteristics of bureaucracy and feministic organization which can be found in kindergarten are analyzed from the standpoint of Ashcraft’s concept «organized dissonance». The author provides some comparisons of bureaucratic organization, feministic organization, and organized dissonance based on such parameters as organizational goals, structure of power, rules, division of labour, status of workers, required skills and competences, and relationships between colleagues.To understand the connection between emotionality and formal rules in kindergarten Konobeeva uses the data collected from participant observation which was conducted at one of public kindergartens in Moscow from 2 April to 12 May 2012. The data include dairy notes and official documents analyzed with the help of open and structured coding.The author concludes that emotionality and formal rules of kindergarten as an organization are intertwined, and they restrain each other and thereby modify practices and participants’ relationships in kindergarten.